Identifying the sources of the slowdown in growth: Demand vs. supply - Nicolò Maffei-Faccioli (Norges Bank, 2021)
Long-run GDP growth has declined in the United States over the past two decades. Two competing views take the stage in accounting for this slowdown: demand-side and supply-side. I empirically quantify their relative importance in a Bayesian SVAR with common trends, identified using sign restrictions based on the co-movement of prices and quantities. While supply-side factors were the main driver of long-run GDP growth prior to 2000, demand-side factors explain half of its slowdown afterwards. The findings suggest a relevant role of demand forces as drivers of long-run growth.
hdl:11250/2783876
Keywords: C32; E3; O47; 330; Long-run growth; Super-hysteresis; SVAR